Thermal Characterization of the Overload Carbon Resistors - Ivana Kostić; Ljubiša Tomić; Aleksandar Kovačević; Saša Nikolić (International Journal of Photoenergy)
In many applications, the electronic component is not continuously but only intermittently overloaded (e.g., inrush current, short circuit, or discharging interference). With this paper, we provide insight into carbon resistors that have to hold out a rarely occurring transient overload. Using simple electrical circuit, the resistor is overheating with higher current than declared, and dissipation is observed by a thermal camera.